USE OF ROSUVASTATIN AS A GEROPROTECTOR IN PEOPLE ENGAGED IN NATURAL GAS PRODUCING - A. T. Abdrashitova; T. N. Panova; I. A. Belolapenko; M. V. Frenkel (Рациональная фармакотерапия в кардиологии)
Background. Prolong contact with manufacturing factors of gas producing, in particular hydrogen sulfide, results in dysfunction of various organs and systems, including immune system, which is involved in regulation of the aging process activity. Absence of effective geropreventive means creates the need for pathogenetic way for aging process deceleration. Aim. To study the geroprotective properties of rosuvastatin in respect of people engaged in the gas producing. Material and Methods. The male workers (n=100) of the company “Gazprom dobycha Astrakhan” were examined. Evaluation of biological age by the method of Chebotarev D.F ., determination of p53 protein and interleukin-8, 10, 18 concentrations by solid phase enzyme immunoassay were performed before treatment start and after 18 months of rosuvastatin taking. Results. Rosuvastatin therapy in dose of 5 mg/day resulted in the reduction in atherogenic lipids, pro-inflammatory cytokine - interleukin-8 and marker of apoptosis - protein p53 as well as aging rate slowdown. Conclusion. Pathogenic method of geroprevention with rosuvastatin 5 mg/day was proposed for people engaged in gas producing.